Rationale, design and baseline data of a mixed methods study examining the clinical impact of a brief transition programme for young people with juvenile idiopathic arthritis: the DON'T RETARD project. Issue 12 (2nd December 2013) - Hilderson, Deborah; Westhovens, Rene; Wouters, Carine; Van der Elst, Kristien; Goossens, Eva; Moons, Philip
Abstract : Objectives: To describe (1) the content of a transition programme for young people with juvenile idiopathic arthritis (JIA) designed as a brief intervention, (2) the rationale and design of a mixed-methods study evaluating the clinical impact of this transition programme and (3) to provide baseline data of the intervention group. Design: An 'embedded experimental' design is used for the evaluation of the transition programme. A 'one-group pretest-posttest, with a non-equivalent posttest-only comparison group design' is used to quantitatively evaluate the impact of the transition programme, applying both longitudinal and comparative analyses. Subsequently, experiences of adolescents and their parents who participated in the experimental group will be analysed qualitatively using content analysis. Setting: Participants in the intervention are recruited at a tertiary care centre in Belgium. The comparison group participants are recruited from one tertiary and three secondary care centres in Belgium. Participants: The intervention group consists of 33 young people (25 females; 8 males) with a median age of 16 years. Main diagnoses are persistent or extended oligoarticular JIA (33%), polyarticular JIA (30%), enthesitis-related JIA (21%) or systemic arthritis (15%). Intervention: The transition programme comprises eight key components: (1) transition coordinator; (2) providing information and education; (3) availability by telephone; (4) information about and contact with an adult care programme; (5) guidance of parents; (6) meeting with peers; (7) transfer plan; and (8) actual transfer to adult care. Primary and secondary outcomes: The primary outcome is health status, as perceived by the adolescents. Secondary outcomes are health status, as perceived by the parents; medication adherence; illness-related knowledge; quality of life; fatigue; promotion of independence; support of autonomy; behavioural control and psychological control. Results: At baseline, the median score was 69.2 (Q1=60.0;Q3=92.9) on psychosocial health and 68.8 (Q1=56.3; Q3=89.1) on physical health. Rheumatic-specific health scores ranged from 62.5 to 100. Conclusions: We present the rationale and design of a study intended to evaluate a transition programme for adolescents with JIA as a brief intervention.